2008
DOI: 10.1073/pnas.0804123105
|View full text |Cite
|
Sign up to set email alerts
|

Class 1A PI3K regulates vessel integrity during development and tumorigenesis

Abstract: PI3K is important in the regulation of growth, proliferation, and survival of tumor cells. We show that class 1A PI3K is also critical in the tumor microenvironment by regulating the integrity of the tumor vasculature. Using Tie2Cre-mediated deletion of the PI3K regulatory subunits (p85␣, p55␣, p50␣, and p85␤), we generated mice with endothelial cell-specific loss of class 1A PI3K. Complete loss of all subunits caused acute embryonic lethality at E11.5 due to hemorrhaging, whereas retention of a single p85␣ al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 37 publications
(44 reference statements)
6
73
0
Order By: Relevance
“…These data were consistent with previously published data demonstrating that PI3K determines heart size in mice (Shioi et al, 2000). Furthermore, the data corroborated studies of others demonstrating that PI3K class IA was required for cardiovascular differentiation in mouse embryos in the presence of VEGF (Luo et al, 2005;Yuan et al, 2008), and in differentiating ES cells where VEGF was found to significantly 1826 Journal of Cell Science 124 (11) enhance a-MHC, cardiac troponin I and Nkx2.5 expression (Chen et al, 2006).…”
Section: Discussionsupporting
confidence: 82%
“…These data were consistent with previously published data demonstrating that PI3K determines heart size in mice (Shioi et al, 2000). Furthermore, the data corroborated studies of others demonstrating that PI3K class IA was required for cardiovascular differentiation in mouse embryos in the presence of VEGF (Luo et al, 2005;Yuan et al, 2008), and in differentiating ES cells where VEGF was found to significantly 1826 Journal of Cell Science 124 (11) enhance a-MHC, cardiac troponin I and Nkx2.5 expression (Chen et al, 2006).…”
Section: Discussionsupporting
confidence: 82%
“…It was shown that PDK1 plays an essential role in regulating endothelial cell migration in response to VEGF-A stimulation (34). Recently, it was shown that PI3K KO mice displayed defects in angiogenesis and vascular integrity (19,44). In these mice, the activation of Akt was impaired, which is the possible cause for vascular abnormalities (19,44).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that PI3K KO mice displayed defects in angiogenesis and vascular integrity (19,44). In these mice, the activation of Akt was impaired, which is the possible cause for vascular abnormalities (19,44). Previously, we studied the Akt1 and Akt3 double knockout (DKO) mice (41,43).…”
Section: Discussionmentioning
confidence: 99%
“…PI3K can be actively recruited and activated by angiogenic factors (35,36). PI3K inhibitors are, therefore, expected to display some degree of antiangiogenic activity.…”
Section: Nvp-bkm120 Possesses Antiangiogenic Activities In Vivomentioning
confidence: 99%